SSR Markers for Quercus suber Tree Identification and Embryo Analysis - GÓMEZ, A; Pintos, B; Aguiriano, E; Manzanera, J A; Bueno, M A (Journal of Heredity, 2001)
Three Quercus simple sequence repeat (SSR) markers were amplified by polymerase chain reaction (PCR) from nuclear DNA extracts of trees and in vitro-induced haploid embryos from anther cultures of Quercus suber L. These markers were sufficiently polymorphic to identify 10 of 12 trees located in two Spanish natural areas. The same loci have been analyzed in anther-derived haploid embryos showing the parental tree allele segregation. All the alleles were present in the haploid progeny. The presence of diverse alleles in embryos derived from the same anther demonstrated that they were induced on multiple microspores or pollen grains and they were not clonally propagated. Also, diploid cultures and mixtures of haploid-diploid tissues were obtained. The origin of such cultures, either somatic or gametic, was elucidated by SSR markers. All the embryos showed only one allele, corroborating a haploid origin. Allelic composition of the haploid progeny permitted parental identification among all analyzed trees.
10.1093/jhered/92.3.292
Keywords: haploid embryos; identification (PG); Quercus suber; SSR markers

Embriogénesis gamética para obtención de haploides en alcornoque. - Bueno, A; GÓMEZ, A; Boscaiu, M; Manzanera, J A; Vicente, O (II Congreso Forestal Español, 1997)
Inducción of haploid embryos and regeneration of plantlets have been obtained for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by culture at 25°C in a simple agar medium without growth regulator.s. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytic development of the microspores and for the induction of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that like most forest trees, are still recalcitrant in anther culture.
Keywords: anther culture; Cork oak; Haploid plants; Stress